Los fundamentos espaciales de las relaciones económicas mundiales - Klaveren, Jacob J. van (1956)
The key to the understanding of Money movements is given by the difference existing between settlement spaces and transportation spaces. The former is a contiguously settled space within which money movements are of an osmotic nature, viz, money flows as liquid does in compensating differences of pressure within a cellular tissue. Settlement spaces only exist on land and their extension depends on the earth`s surface configuration. A transportation space, on the contrary, can over land and sea and its extension, being chiefly determined by technical progress, has grown considerably in the course of history. Part of the transportation spaces coincide with the settlement spaces, the other part bridging the gaps between them. Inside a transportation space money moves by leaps and bounds and there is no guarantee that natural compensatory flows, crossing the gaps between the different settlements spaces, will be instigated. Only in case of an incidental perfect harmony between their respective economic structures could such an automatic adjustment be relied upon. However, their economic structures depend primarily on internal conditions, so that disharmonies are the rule and drains in one direction to another must ensue. If a settlement space is completely covered by transportation spaces we say that an economic space has developed. Like the settlement space it is therefore separated by gaps from other economic spaces, thus forming a natural interior market. Inside an economic space transportation movements of money may also occasion drains, but their volume is limited by the harmony imposed by spatial interdependence and is moreover mitigated by compensatory osmotic flows. Whilst political boundaries, at least in Europe, have changed little in the last century, the economic and transportation spaces have grown considerably. This explains why efforts are being made to reach an "integration". Aiming at unifying the artificially segregated "home" markets in order to create an unfettered economic space, which is the natural interior market. However, we find many inconsistencies and lack of clarity in the discussion on this topic, as politicians are guided rather by political than by economic considerations. Ignoring spatial relationships these are often incompatible with true integration, going so far as to try to achieve the membership of unwilling nations which are located in other spaces.